2005
DOI: 10.1583/04-1490mr2.1
|View full text |Cite
|
Sign up to set email alerts
|

Extension of Dissection in Stent-Graft Treatment of Type B Aortic Dissection:Lessons Learned from Endovascular Experience

Abstract: Endovascular treatment is becoming the most important treatment modality in the complex management of type B dissection, providing benefits to both acute and chronic patients. Growing technical experience and improving stent-graft devices have resulted in better patient outcome and expanded clinical indications. Nevertheless, similar to any treatment option, this less invasive method has its inherent risks. Several cases of iatrogenic dissection have been reported in the literature, underlying the need for gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 34 publications
2
36
0
Order By: Relevance
“…10,11 Indeed, in 40 of the 48 (83%) patients of our series stent grafts with proximal bare springs were used. Moreover, in patients in whom rAAD was classified as being stent graftinduced, proximal bare spring stent grafts were used in 27 of 29 patients (93%).…”
Section: Eggebrecht Et Al Ascending Aortic Dissection After Tevar S279mentioning
confidence: 95%
See 2 more Smart Citations
“…10,11 Indeed, in 40 of the 48 (83%) patients of our series stent grafts with proximal bare springs were used. Moreover, in patients in whom rAAD was classified as being stent graftinduced, proximal bare spring stent grafts were used in 27 of 29 patients (93%).…”
Section: Eggebrecht Et Al Ascending Aortic Dissection After Tevar S279mentioning
confidence: 95%
“…10,11 Previous reports have estimated the risk of rAAD after TEVAR to range between 1.9% and 2.4% 1,10,11 to as high as 6.8% 9 in a single-center experience involving a relatively small number of procedures. The incidence of TEVAR-related dissection was low in the current study and perhaps represents a much more stable estimate of this event due to the large number of patients evaluated.…”
Section: Eggebrecht Et Al Ascending Aortic Dissection After Tevar S279mentioning
confidence: 99%
See 1 more Smart Citation
“…Injury of the aortic wall in this part of aorta may have fatal consequences such as a retrograde type A aortic dissection (RAAD) or aortic rupture. The incidence of RAAD following TEVAR has been reported to be between 1.3% and 6.8% (9)(10)(11).…”
Section: Indications and Contraindicationsmentioning
confidence: 99%
“…In the past, TEVAR was positioned as the main treatment strategy for TAA or traumatic aortic transection after its clinical introduction in 1994 [16]. Various studies demonstrated that the minimally invasive procedure of TEVAR might allow rapid control of blood loss even in patients with hemodynamic instability [17,18], and that the perioperative morbidity of TEVAR during an urgent condition was significantly better than that of emergency open surgery [19]. After the usefulness of TEVAR in closing a fistula between the aorta and an adjacent organ was reported in 1996 [20], numerous promising results in its short-term effectiveness have encouraged its clinical use, and the indications of TEVAR have expanded to AEF.…”
Section: Etiologies Of Aorto-esophageal Fistulamentioning
confidence: 99%